Cattle focus reaps rewards - Chigaru, P.R.N. (1989)
Highlights ILCA's cattle milk and meat research. Discusses the different research projects including reproductive wastage & hygiene management, feeding and management systems, milk preservation and processing, economics of cattle production, and establishment of the cattle research network.